Ultrashort dual colour laser at 1.55 and 1.88 μ m by using a carbon nanotube saturable absorber - Hussain, SA (IEEE, 2019)
In this letter, we have achieved passive mode-locked lasers at 1.55 and 1.88 μm that can provide ultrashort (pulse duration ~1 ps) pulses by using a single carbon nanotube (CNT) saturable absorber. The fiber cavity that has been constructed is compact, simple, and stable against mechanical perturbation, which makes this laser superior to solid-state lasers. This letter has shown that a CNT saturable absorber is an alternative to graphene and has two mode-locked wavelengths that are approximately 250 nm apart. The resultant laser is useful for applications where compact dual color wavelengths are required.